SOSIALISASI PENGELOLAAN BANJIR BANDANG BERBASIS MASYARAKAT DALAM MITIGASI BENCANA DI KABUPATEN CILACAP - Wildan Herwindo; Ingerawi Sekaring Bumi; Wahyu Prasetyo; Syamsul Bahri; Tia Hetwisari (Politeknik Negeri Sriwijaya, 2023)
Limbangan Village is located at the Wanareja District, Cilacap Regency, Central Java. It is one of the areas prone to flash floods. Based on data, flash floods were recorded on 27 October 2021 which were caused by the overflow of the Cigeugeumeuh River and resulted in hundreds of houses and markets being damaged. Therefore, to reduce losses due to disasters that occur, especially flash floods in Limbangan Village, mitigation efforts are carried out in the form of socialization of community-based management of flash floods. Efforts to carry out community-based flood management in Cilacap Regency, were carried out through collaboration between the Public Works Polytechnic and Limbangan Village. The socialization of flood management in Limbangan Village uses concept of participatory rural community social approach or Participatory Rural Appraisal (PRA). At the end, community service activities in Cilacap Regency by the Public Works Polytechnic, Semarang have been successfully held. The results achieved in the implementation of this community service are the provision of information on rainfall that has the potential to cause flash floods, the learning process of disaster mitigation as a preparedness measure for flash floods, flood-prone and evacuation maps, and communication tools as a continuation of the community service program.